Elite Influence? Religion, Economics, and the Rise of the Nazis - Jörg Spenkuch; Philipp Tillmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Adolf Hitler's seizure of power was one of the most consequential events of the twentieth century. Yet, our understanding of which factors fueled the astonishing rise of the Nazis remains highly incomplete. This paper shows that religion played an important role in the Nazi party's electoral success—dwarfing all available socio-economic variables. To obtain the first causal estimates we exploit plausibly exogenous variation in the geographic distribution of Catholics and Protestants due to a peace treaty in the sixteenth century. Even after allowing for sizeable violations of the exclusion restriction, the evidence indicates that Catholics were significantly less likely to vote for the Nazi Party than Protestants. Consistent with the historical record, our results are most naturally rationalized by a model in which the Catholic Church leaned on believers to vote for the democratic Zentrum Party, whereas the Protestant Church remained politically neutral.
Keywords: Z12; N34; D72; 330